Elastic sand blasting sand grain and preparation method thereof

By using composite sand blasting sand particles composed of abrasives, elastic resins and coupling agents, the problem of the existing sand blasting technology having a high impact on the workpiece is solved, efficient polishing and processing of the workpiece is achieved, and service life is extended.

CN119684970APending Publication Date: 2025-03-25NANJING UNIV OF AERONAUTICS & ASTRONAUTICS
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411848690.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing sandblasting technology has a large impact on the workpiece during processing, which can easily cause damage to the workpiece, and the elastic media is easily damaged during use, affecting the service life.

Method used

The composite sand blasted sand particles composed of abrasives, elastic resins and coupling agents are used to prepare sand blasted sand particles with good elasticity through group design, preferential elastomer and curing agent, and optimization of the curing process.

Benefits of technology

Effective polishing and processing of the workpiece surface is achieved, impact force is reduced, service life is extended, and processing efficiency is improved in terms of deburring, paint removal, rust removal, etc.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119684970A_ABST
    Figure CN119684970A_ABST
Patent Text Reader

Abstract

The invention relates to an abrasive particle-containing composite sand grain for elastic sand blasting and a preparation method thereof. The abrasive particle-containing composite sand grain for elastic sand blasting is characterized by consisting of an elastic matrix and abrasive particles, the preparation method comprises the following steps: (1) mixing and uniformly stirring the high-elasticity liquid resin and the low-elasticity resin; (2) adding a grinding material into the resin and uniformly mixing; (3) adding a coupling agent into the mixture; (4) sequentially adding a curing agent and a curing accelerator into the mixture, stirring by using a stirrer after each addition, and uniformly mixing; (5) putting the mixture into a mold, and putting the mold into a drying box for heating and curing; and (6) taking out the cured composite sand grain block, crushing and screening. The elastic sand blasting sand grain has good elasticity, and reliable combination of an abrasive material and an elastic base body is achieved. And higher machining efficiency and better machining effect and polishing effect are achieved in the aspects of deburring, rust removal, paint removal and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a technology for preparing abrasives and abrasive processing (deburring, descaling, rust removal and polishing), in particular to a technology for preparing composite sandblasting sand grains with good elasticity, specifically to a technology for preparing composite sandblasting sand grains with good elasticity and a method for preparing the same. Background Art

[0002] Sandblasting is a surface processing technology with a long history. Its main structural principle is to use a sandblasting machine to use compressed air in a pipeline to transport powdered granular materials from the sand inlet pipe to the sandblasting pipe. The sand particles are pushed forward by the compressed air in the pipeline. In the process of converting kinetic energy into potential energy, the high-speed moving granular materials flow quickly to the surface of the workpiece, thereby improving the surface quality of the object. Compressed air is ejected from the nozzle of the spray gun at a certain flow rate and pressure, and is ejected together with the sand particles, acting on the surface of the workpiece to remove burrs, paint, rust, and strengthen the workpiece.

[0003] Different types of powdered particles used in sandblasting machines can achieve different effects. Traditional sandblasting mostly uses steel sand, aluminum oxide, quartz sand, silicon carbide, etc., but quartz sand is the most widely used. Most of this sand body is used in metal surface treatment processes (paint removal, rust removal, oxide skin removal, burr removal, etc.). For example, a surface treatment device for magnesium-aluminum alloy processing invented by Anhui Yunhai Magnesium Co., Ltd. (patent number: CN 202410973084.0) uses sandblasting technology to treat the oxide skin on the surface of the alloy. The use of new elastic sandblasting sand particles has greatly expanded the application scenarios and scope of sandblasting. For example, an elastic sandblasting ball for polishing the surface of dental ceramic restorations invented by Zhejiang Erran Company (patent number: CN205286570 U) introduced elastic sandblasting technology into the medical field, solving the problem that the diamond sandblasting material used for sandblasting and polishing of dental restorations is hard and easy to cause cracks in the restoration during polishing, resulting in excessive wear of natural teeth.

[0004] At present, most of the elastic sandblasting grits on the market are prepared by adding elastic media between hard abrasives to give them a certain buffering capacity to reduce the impact on the workpiece surface, or using elastic foam materials to cover the rigid abrasives to play a buffering role, such as Qingdao Shamu International Trade Co., Ltd.'s elastic abrasive for sandblasting (patent number: CN 101892014 A).

[0005] However, the several preparation methods mentioned above all have the following problems. First, because the elastic medium can only provide limited elastic force, the impact force on the workpiece surface is still relatively large, which can easily cause damage to the workpiece; secondly, the elastic medium is exposed to the outside and is easily damaged due to the strong impact force during actual use, which affects the service life. The elastic sandblasting sand grains prepared by the present invention use elastic resin as the matrix, and hard abrasives evenly cover the surface of the matrix to play a cutting role in actual processing. When the elastic sand grains impact the workpiece surface, the impact force of the sand grains will be greatly buffered due to the presence of a large amount of elastic resin, thereby solving the problems of easy damage to the workpiece and easy breakage of the above-mentioned elastic abrasives, and realizing the organic combination of elastomers and hard abrasives, which has excellent development prospects and commercial value. Summary of the invention

[0006] The purpose of the present invention is to solve the problem that the existing sandblasting technology is limited to the fields of paint removal, rust removal, burr removal, etc., and the hard sand particles have a large impact force on the workpiece, thereby causing unnecessary surface damage to the workpiece surface. A composite sandblasting sand particle with good elasticity is invented, and a corresponding preparation method is provided. The present invention obtains sandblasting sand particles with good elasticity through a series of processes such as group design, elastomer optimization, coupling agent, curing agent, curing accelerator optimization, and curing scheme optimization, which can be used in the fields of metal material paint removal, rust removal, oxide skin removal, polishing and other processing technologies.

[0007] One of the technical solutions of the present invention is: A composite sandblasting grit with good elasticity, characterized in that it is composed of abrasive, high-elasticity liquid resin and low-elasticity resin, wherein the mass percentage of the abrasive is 1% to 18%, the mass percentage of the high-elasticity liquid resin is 47% to 74%, the mass percentage of the low-elasticity resin is 16% to 49%, and the sum of the components is 100%.

[0008] The abrasive is a combination of one or more of cubic boron nitride, diamond, silicon carbide or aluminum oxide.

[0009] The particle size of the abrasive particles is distributed between 0.5 and 10 μm.

[0010] The elastic modulus of the highly elastic liquid resin is between 5 and 50 MPa.

[0011] The elastic modulus of the low-elasticity resin is between 100 and 500 MPa.

[0012] The low-elasticity resin is a powder with a particle size of 10 μm to 100 μm.

[0013] The second technical solution of the present invention is: A method for preparing composite sandblasting sand particles with good elasticity, characterized in that it comprises the following steps; (1) Preparing a high-elasticity liquid resin and a low-elasticity resin in proportion and mixing them evenly to obtain a mixed resin; (2) adding abrasive to the obtained mixed resin and mixing them evenly to obtain an abrasive-containing mixed resin; (3) adding coupling agents to the mixed resin containing abrasives in sequence and mixing them evenly to obtain a mixed resin containing coupling agents and abrasives; (4) adding a curing agent and a curing accelerator to the mixed resin containing a coupling agent and an abrasive in sequence, and stirring the mixture with a stirrer after each addition to obtain a mixture to be cured; (5) pouring the mixture to be cured into a mold, placing it in a drying oven, heating it to cure it, taking it out after curing and pressurizing it into a block, and placing it in the drying oven again to cure it, thereby obtaining a cured composite sand block; (6) Take out the solidified composite sand blocks, crush and screen them.

[0014] In the step (1), the high elastic liquid resin and the low elastic resin are mixed by stirring with a stirrer, and the speed of the stirrer is 500-1500 r / min.

[0015] In step (3), the main component of the coupling agent is YR-Si(OR)3, which is added in a proportion of 0.5% of the resin mass and mixed evenly.

[0016] In step (4), the main component of the curing agent is cumene hydroperoxide, which is added in a proportion of 1.0% of the resin mass and mixed evenly; the main component of the curing accelerator is cobalt cyclohexaneate, which is added in a proportion of 0.5% of the resin mass and mixed evenly.

[0017] In the step (5), the curing temperature is 100-200°C, the curing time is 15-30 minutes, and then the product is taken out. The pressurization pressure is 0.4-1.2 kPa, and the re-curing time is 5-10 minutes.

[0018] In the step (6), the crushed sand particles after solidification are sieved using a sieve with a mesh size of 5 to 80.

[0019] The third technical solution of the present invention is: A composite sandblasting grit with good elasticity is characterized in that it is used in the surface processing field of various metal materials, and the processing field includes deburring, descaling, rust removal, polishing and the like.

[0020] The beneficial effects of the present invention are: The present invention obtains sandblasting sand particles with good elasticity through a series of processes such as elastic matrix, curing agent, coupling agent, curing accelerator optimization, and curing process optimization. The sandblasting sand particles can be used for deburring, descaling, rust removal, polishing and other processing technologies of various metal materials, especially in the field of polishing technology for complex cavities.

[0021] The sandblasting sand particles with good elasticity of the present invention can realize the polishing process of various hard metals and non-metallic materials that cannot be completed by ordinary elastic sandblasting particles; and have higher processing efficiency and better effects in deburring, paint removal, rust removal, oxide skin removal, etc. Secondly, the composite elastic abrasive described in the present invention can complete the polishing process of complex cavities, solve the limitations of the industry at this stage for complex cavity processing, and provide a new complex cavity polishing process technology with complete intellectual property rights. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a stereomicroscope image of the sandblasting sand grains with good elasticity of the present invention, showing the morphology of the sandblasting sand grains after solidification and crushing, and the abrasive and the elastic resin are well combined to form composite sandblasting sand grains with good elasticity.

[0023] Figure 2 This is a stereomicroscope image of the elastic sandblasting grains containing no abrasive in Comparative Example 1. Specific implementation plan

[0024] The present invention is further described below with reference to the accompanying drawings and examples.

[0025] Example 1.

[0026] A composite sandblasting grit with good elasticity is made of 60g of 0.5-5μm diamond micropowder and 300g of high-elasticity liquid resin and low-elasticity mixed resin. The preparation method is as follows: 300g of high-elasticity liquid resin (240g) and low-elasticity resin (60g) of 10-40μm are prepared in a ratio of 4:1, and mixed evenly; 60g of diamond (20% of the mass of the mixed resin) is added to the mixture, and mixed evenly; 1.5g of coupling agent (0.5% of the mass of the mixed resin) is added to the mixture in sequence, and mixed evenly. ; Add 3g of curing agent (1% of the mass of the mixed resin) and 1.5g of curing accelerator (0.5% of the mass of the mixed resin) in sequence, and stir with a mixer after each addition to make the mixture uniform; pour the above mixture into a mold, put it into a drying oven, heat it to 100°C for curing, take it out after curing for 15 minutes, pressurize it to 0.4kPa, and put it into the drying oven again for curing for 10 minutes; take out the cured composite sand block, break it, and sieve it with a 40-80 mesh screen to obtain sandblasting sand with good elasticity. The stereomicroscope of the obtained sand is as follows Figure 1As shown. The elastic sandblasting grit was used to polish TC4 titanium alloy. The spraying pressure was 0.4MPa, the spraying time was 150s, the average surface roughness was 255nm, and the surface gloss was Gs (60°) = 56.5GU.

[0027] Comparative Example 1. like Figure 2 The difference between this comparative example and implementation 1 is that the sandblasting sand grains are prepared without diamond, and the other parameters are the same. The sand grains are used to process TC4 titanium alloy, the spraying pressure is 0.4MPa, the spraying time is 150s, and the surface roughness is 617nm, and the surface gloss is Gs (60°) = 13GU.

[0028] Example 2.

[0029] A composite sandblasting grit with good elasticity is made of 60g of 0.5-5μm diamond micropowder and 300g of high-elasticity liquid resin and 10-40μm low-elasticity mixed resin. The preparation method is as follows: 300g of high-elasticity liquid resin (200g) and low-elasticity resin (100g) are prepared in a ratio of 2:1, and mixed evenly; 60g of diamond (20% of the mass of the mixed resin) is added to the mixture, and mixed evenly; 1.5g of coupling agent (0. 5%), mix evenly; add 3g curing agent (1% of the mass of the mixed resin) and 1.5g curing accelerator (0.5% of the mass of the mixed resin) in sequence, and stir with a mixer to mix evenly after each addition; pour the above mixture into the mold, put it into the drying oven, heat it to 150℃ for curing, take it out after curing for 20 minutes, pressurize it with 0.8kPa, and put it into the drying oven again for curing for 5 minutes; take out the cured composite sand block, crush it and sieve it with a 5~30 mesh screen to obtain sandblasting sand with good elasticity. Use this elastic sandblasting sand to polish TC4 titanium alloy. The injection pressure is 0.4MPa, the injection time is 150s, the average surface roughness is 297nm, and the surface gloss is Gs (60°) = 54GU.

[0030] Example 3.

[0031] A composite sandblasting grit with good elasticity is made of 33g of 2-4μm diamond powder (accounting for 1% of the mass percentage of 333g of finished product) and 300g of high-elasticity liquid resin and 10-40μm low-elasticity mixed resin. The preparation method is as follows: 300g of high-elasticity liquid resin (225g) and low-elasticity resin (75g) are prepared in a ratio of 3:1, and mixed evenly; 33g of diamond (10% of the mass of the mixed resin) is added to the mixture, and mixed evenly; 1.5g of coupling agent (mixed resin) is added to the mixture in sequence; 1.5g of coupling agent (mixed resin) is added to the mixture ... 0.5% of the mass of lipid), mix evenly; add 3g of curing agent (1% of the mass of mixed resin) and 1.5g of curing accelerator (0.5% of the mass of mixed resin) in sequence, and stir with a mixer to mix evenly after each addition; pour the above mixture into the mold, put it into the drying oven, heat it to 100℃ for curing, take it out after curing for 10 minutes, pressurize it with 0.6kPa, and put it into the drying oven again for curing for 15 minutes; take out the cured composite sand block, break it and sieve it with a 40~80 mesh screen to obtain sandblasting sand with good elasticity. Use this elastic sandblasting sand to polish TC4 titanium alloy. The injection pressure is 0.4MPa, the injection time is 150s, the average surface roughness is 262nm, and the surface gloss is Gs (60°) = 54.5GU.

[0032] Example 4.

[0033] A composite sandblasting sand grain with good elasticity is made of 15g of 5-10μm silicon carbide micropowder and 300g of high-elasticity liquid resin and 40-100μm low-elasticity mixed resin. The preparation method is as follows: 300g of high-elasticity liquid resin and low-elasticity resin are prepared in a 1:1 ratio and mixed evenly; 15g of silicon carbide (5% of the mass of the mixed resin) is added to the mixture and mixed evenly; 1.5g of coupling agent (0.5% of the mass of the mixed resin) is added to the mixture in sequence and mixed evenly. ; Add 3g of curing agent (1% of the mass of the mixed resin) and 1.5g of curing accelerator (0.5% of the mass of the mixed resin) in sequence, and stir with a mixer after each addition to make it evenly mixed; pour the above mixture into the mold, put it into the drying oven, heat it to 150℃ for curing, take it out after curing for 30 minutes, pressurize it with 0.8kPa, and put it into the drying oven again for curing for 15 minutes; take out the cured composite sand block, break it and sieve it with a 5~40 mesh screen to obtain sandblasting sand with good elasticity. Use this elastic sandblasting sand to deburr 202 stainless steel parts. The injection pressure is 0.8MPa. According to statistics, there are no obvious burrs on the surface and edge of the stainless steel after 64S using a magnifying glass, and there is no bulge or roughness when touched by hand.

[0034] Example 5.

[0035] A composite sandblasting sand grain with good elasticity is made of 5.5g of 5-10μm silicon carbide (accounting for 18% of the mass percentage of 305.5g of the finished product) and 300g of a high-elasticity liquid resin and a low-elasticity mixed resin of 40-100μm. The preparation method is as follows: 300g of the high-elasticity liquid resin and the low-elasticity resin are prepared in a 1:1 ratio and mixed evenly; 6g of silicon carbide (2% of the mass of the mixed resin) is added to the mixture and mixed evenly; 1.5g of a coupling agent (10% of the mass of the mixed resin) is added to the mixture in sequence; 0.5%), mix evenly; add 3g curing agent (1% of the mass of the mixed resin) and 1.5g curing accelerator (0.5% of the mass of the mixed resin) in sequence, and stir with a mixer to mix evenly after each addition; pour the above mixture into the mold, put it into the drying oven, heat it to 100℃ for curing, take it out after curing for 10 minutes, pressurize it to 0.8kPa, and put it into the drying oven again for curing for 15 minutes; take out the cured composite sand block, break it and sieve it with a 5~40 mesh screen to obtain sandblasting sand with good elasticity. Use this elastic sandblasting sand to deburr 202 stainless steel parts. The injection pressure is 1.2MPa. According to statistics, there are no obvious burrs on the surface and edge of the stainless steel after 51S using a magnifying glass, and there is no bulge or roughness when touched by hand.

[0036] Example 6.

[0037] A composite sandblasting sand grain with good elasticity is made of 15g of 5-10μm aluminum oxide and 300g of a high-elasticity liquid resin and a 40-100μm low-elasticity mixed resin. The preparation method is as follows: 300g of the high-elasticity liquid resin and the low-elasticity resin are prepared in a ratio of 2:1, and mixed evenly; 15g of aluminum oxide (5% of the mass of the mixed resin) is added to the mixture, and mixed evenly; 1.5g of a coupling agent (0.5% of the mass of the mixed resin) is added to the mixture in sequence, and mixed evenly; Add 3g of curing agent (1% of the mass of the mixed resin) and 1.5g of curing accelerator (0.5% of the mass of the mixed resin) in sequence, and stir with a mixer after each addition to make it evenly mixed; pour the above mixture into the mold, put it into the drying oven, heat it to 100℃ for curing, take it out after curing for 10 minutes, pressurize it with 0.8kPa, and put it into the drying oven again for curing for 15 minutes; take out the cured composite sand block, crush it and sieve it with a 5-40 mesh screen to obtain sandblasting sand with good elasticity. Use this elastic sandblasting sand to descale TC4 titanium alloy. The injection pressure is 0.8MPa. According to statistics, the surface of the titanium alloy is silver-gray and has a metallic luster after 32S, and the black covering layer on the surface is completely removed.

[0038] Example 7.

[0039] A composite sandblasting sand grain with good elasticity is made of 15g of 5-10μm aluminum oxide and 300g of high-elasticity liquid resin and 40-100μm low-elasticity mixed resin. The preparation method is as follows: 300g of high-elasticity liquid resin and low-elasticity resin are prepared in a ratio of 2:1, and mixed evenly; 15g of aluminum oxide (5% of the mass of the mixed resin) is added to the mixture, and mixed evenly; 1.5g of coupling agent (0.5% of the mass of the mixed resin) is added to the mixture in sequence, and mixed evenly. ; Add 3g of curing agent (1% of the mass of the mixed resin) and 1.5g of curing accelerator (0.5% of the mass of the mixed resin) in sequence, and stir with a mixer after each addition to make it evenly mixed; Pour the above mixture into the mold, put it into the drying oven, heat it to 150℃ for curing, take it out after curing for 20 minutes, pressurize it with 1.0kPa, and put it into the drying oven again for curing for 15 minutes; Take out the cured composite sand block, break it and sieve it with a 5~40 mesh screen to obtain sandblasting sand with good elasticity. Use this elastic sandblasting sand to remove rust from the surface of high carbon steel T10. The spraying pressure is 1.2MPa. After 19S, the reddish brown color of the T10 surface completely fades and becomes silver-gray, and no blue precipitation appears after a drop of potassium ferrocyanide solution is dropped on its surface, proving that the rust is completely removed.

[0040] Example 8.

[0041] A composite sandblasting sand grain with good elasticity is made of 6g of 5-10μm aluminum oxide and 300g of a high-elasticity liquid resin and a low-elasticity mixed resin of 40-100μm. The preparation method is as follows: 300g of the high-elasticity liquid resin and the low-elasticity resin are prepared in a ratio of 4:1, and mixed evenly; 6g of aluminum oxide (2% of the mass of the mixed resin) is added to the mixture, and mixed evenly; 1.5g of a coupling agent (0.5% of the mass of the mixed resin) is added to the mixture in sequence, and mixed evenly; Add 3g of curing agent (1% of the mass of the mixed resin) and 1.5g of curing accelerator (0.5% of the mass of the mixed resin) in sequence, and stir with a mixer after each addition to make it evenly mixed; pour the above mixture into the mold, put it into the drying oven, heat it to 150℃ for curing, take it out after curing for 20 minutes, pressurize it with 1.2kPa, and put it into the drying oven again for curing for 15 minutes; take out the cured composite sand block, break it and sieve it with a 5-40 mesh screen to obtain sandblasting sand with good elasticity. Use this elastic sandblasting sand to remove rust from the surface of high carbon steel T10. The spray pressure is 1.2MPa. After 24S, the reddish brown color of the T10 surface completely fades and becomes silver-gray, and no blue precipitation appears after a drop of potassium ferrocyanide solution is dropped on its surface, proving that the rust is completely removed.

[0042] Example 9.

[0043] A composite sandblasting sand grain with good elasticity is made of 12g of 5-10μm aluminum oxide and 300g of a high-elasticity liquid resin and a low-elasticity mixed resin of 40-100μm. The preparation method is as follows: 300g of the high-elasticity liquid resin and the low-elasticity resin are prepared in a ratio of 4:1, and mixed evenly; 12g of aluminum oxide (4% of the mass of the mixed resin) is added to the mixture, and mixed evenly; 1.5g of a coupling agent (0.5% of the mass of the mixed resin) is added to the mixture in sequence, and mixed evenly. ; Add 3g of curing agent (1% of the mass of the mixed resin) and 1.5g of curing accelerator (0.5% of the mass of the mixed resin) in sequence, and stir with a mixer after each addition to make them evenly mixed; Pour the above mixture into the mold, put it into the drying oven, heat it to 150℃ for curing, take it out after curing for 30 minutes, pressurize it with 1.2kPa, and put it into the drying oven again for curing for 15 minutes; Take out the cured composite sand block, break it and sieve it with a 5~40 mesh screen to obtain sandblasting sand with good elasticity. Use this elastic sandblasting sand to carry out the removal test of carbon fiber reinforced resin-based composite materials (CFRP). The spraying pressure is 0.8MPa. After 19S, the CFRP material on the surface of the workpiece is completely removed, and there is no obvious damage to the internal workpiece.

[0044] Example 10.

[0045] A composite sandblasting sand grain with good elasticity is made of 15g of 5-10μm aluminum oxide and 300g of high-elasticity liquid resin and 40-100μm low-elasticity mixed resin. The preparation method is as follows: 300g of high-elasticity liquid resin and low-elasticity resin are prepared in a 1:1 ratio and mixed evenly; 15g of aluminum oxide (5% of the mass of the mixed resin) is added to the mixture and mixed evenly; 1.5g of coupling agent (0.5% of the mass of the mixed resin) is added to the mixture in sequence and mixed evenly. ; Add 3g of curing agent (1% of the mass of the mixed resin) and 1.5g of curing accelerator (0.5% of the mass of the mixed resin) in sequence, and stir with a mixer after each addition to make it evenly mixed; pour the above mixture into the mold, put it into the drying oven, heat it to 150℃ for curing, take it out after curing for 30 minutes, pressurize it with 1.2kPa, and put it into the drying oven again for curing for 15 minutes; take out the cured composite sand block, break it and sieve it with a 5~40 mesh screen to obtain sandblasting sand with good elasticity. Use this elastic sandblasting sand to carry out the removal test of CFRP. The injection pressure is 1.2MPa. After 12S, the CFRP material on the surface of the workpiece is completely removed, and there is no obvious damage to the internal workpiece.

[0046] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0047] The present invention does not involve parts that are the same as the prior art or can be implemented by using the prior art.

Claims

1. A composite sandblasting grit with good elasticity, characterized in that: It consists of abrasive, high-elasticity liquid resin and low-elasticity resin, wherein the mass percentage of the abrasive is 1%~18%, the mass percentage of the high-elasticity liquid resin is 47%~74%, the mass percentage of the low-elasticity resin is 16%~49%, and the sum of all components is 100%.

2. The composite sandblasting grit according to claim 1, characterized in that: The abrasive is a combination of one or more of cubic boron nitride, diamond, silicon carbide or aluminum oxide.

3. The composite sandblasting grit according to claim 1, characterized in that: The particle size of the abrasive particles is distributed between 0.5 and 10 μm.

4. The composite sandblasting grit according to claim 1, characterized in that: The elastic modulus of the highly elastic liquid resin is between 5 and 50 MPa.

5. The composite sandblasting grit according to claim 1, characterized in that: The elastic modulus of the low-elasticity resin is between 100 and 500 MPa.

6. The composite sandblasting grit according to claim 1 or 5, characterized in that: The low-elasticity resin is a powder with a particle size of 10 μm to 100 μm.

7. A method for preparing the composite sandblasting grit with good elasticity as claimed in claim 1, characterized in that; The method comprises the following steps: (1) preparing a high-elasticity liquid resin and a low-elasticity resin in proportion, and mixing them evenly to obtain a mixed resin; (2) adding an abrasive to the obtained mixed resin, and mixing them evenly to obtain an abrasive-containing mixed resin; (3) sequentially adding a coupling agent to the abrasive-containing mixed resin, and mixing them evenly to obtain a mixed resin containing a coupling agent and an abrasive; (4) sequentially adding a curing agent and a curing accelerator to the mixed resin containing a coupling agent and an abrasive, and stirring the mixture with a stirrer after each addition to obtain a mixture to be cured; (5) pouring the mixture to be cured into a mold, placing it in a drying box, heating and curing it, taking it out after curing, pressurizing and curing it into a block, and placing it in the drying box again for curing to obtain a cured composite sand block; (6) taking out the cured composite sand block, and crushing and screening it.

8. The preparation method according to claim 7, characterized in that: In the step (1), the mass ratio of the high elastic liquid resin to the low elastic resin is 1.0-4.0; in the step (3), the coupling agent is a silane coupling agent, the main component of which is YR-Si(OR)3, and the added amount is 0.5% of the mass of the mixed resin; in the step (4), the main component of the curing agent is cumene hydroperoxide, and the added amount is 1% of the mass of the mixed resin; the main component of the curing accelerator is cobalt cyclohexaneate, and the added amount is 0.5% of the mass of the mixed resin; in the step (5), the curing temperature is 100-200°C, the curing time is 15-30 minutes, and then the material is taken out, the pressurized pressure is 0.4-1.2 kPa, and the re-curing time is 5-10 minutes; in the step (6), the composite sand block is crushed and sieved using a 5-80 mesh screen.

9. An application of the elastic sandblasting grit according to claim 1, characterized in that: It is used in the processing of titanium alloy and stainless steel metals.

10. The use according to claim 9, characterized in that: The processing includes deburring, rust removal, deoxidation and polishing processes.

Citation Information

Patent Citations

  • Elastic grinding material for sandblasting treatment

    CN101892014A

  • Surface treatment device for magnesium-aluminum alloy processing

    CN118721038A

  • Dental polishing prosthesis is elasticity sandblast ball for surface finish

    CN205286570U